Nebivolol Ameliorates Nitric Oxide–Deficient Hypertension - L.A. Fortepiani; M.C. Ortiz; N.M. Atucha; Joaquin Garcia-Estan (The Scientific World Journal)
Nebivolol is a new selective beta 1-adrenoceptor antagonist with nitric oxide (NO)–releasing properties. In the present study we have analyzed whether nebivolol affects the development of the arterial hypertension that follows the chronic inhibition of nitric oxide synthesis. Nebivolol (1 mg/kg/day, 14 days) was given concurrently with the NO synthesis inhibitor Nw-nitro-L-arginine methyl ester (L-NAME, 0.1, 1, and 10 mg/kg/day, 14 days) to several groups of rats. Blood pressure, renal function, plasma renin activity (PRA), and NO activity and metabolites were measured at the end of the treatment period. L-NAME treatment alone increased mean arterial pressure dose dependently (103.5 ± 2.4, 110.9 ± 2.0, and 125.8 ± 2.2 mmHg, respectively). Nebivolol completely prevented the development of arterial hypertension in the groups treated with L-NAME at the doses of 0.1 and 1 mg/kg/day and reduced the increase achieved with the L-NAME dose of 10 mg/kg/day (110.3 ± 2.7). There were no differences in glomerular filtration rate or natriuresis between nebivolol-treated and -untreated rats. Plasma nitrates+nitrites and calcium-dependent NO synthase activity in the kidney also decreased dose dependently with L-NAME treatment and nebivolol did not significantly modify it. However, PRA was lower in all groups treated with nebivolol and L-NAME as compared to the rats receiving only L-NAME. These data indicate that nebivolol prevents the development of the arterial hypertension associated with chronic NO deficit and this effect seems to be dependent on the inhibition of renin-angiotensin system.